Motor learning in post stroke subjects: the effects of practice conditions on the temporal synchronization - Camila Torriani-Pasin; Giordano Marcio Gatinho Bonuzzi; Gisele Carla dos Santos Palma; Andrea Michele Freudenheim; Umberto Cesar Corrêa (Universidade Estadual Paulista (UNESP), 2018)
Abstract AIMS The aim of this study was to investigate the effects of practice schedule on the motor learning of a synchronization timing task in post-stroke subjects. Subjects and METHODS Seventeen post-stroke individuals were assigned to the experimental group and for the control group were selected seventeen healthy individuals. At the acquisition phase, all participants performed 30 trials of a coincident timing task. Nine individuals from each group practiced constantly and eight from each group practiced randomly, with speed changes in the task. Subsequent phases included: 1) immediate transfer test and 2) long term transfer test after 3 days. Data were analyzed in relation to absolute, variable, and constant errors to assess the performance concerning accuracy, consistence, and direction of responses, respectively. RESULTS All groups increased their accuracy through the practice and were able to adapt it in different speeds. The stroke subjects were more variable in their motor responses. There was no effect of the practice schedule on motor learning, regardless the presence or absence of the neurologic damage. CONCLUSION Post stroke individuals were able to learn a synchronizing task and the capacity of adapt their performance after speed perturbation was preserved. There was no effect of the practice schedule on motor learning.